Analyzing Gaze Behavior in Complex (Aerial) Skills - Heinen, T.; Velentzas, K.; Vinken, P. M. (International Journal of Sports Science and Engineering, 2012)
Complex skills with aerial phases, such as somersaults or release-regrasp skills make up about 45 % of all elements in artistic gymnastics. The underlying mechanics of these skills have been studied extensively, and visual information is thought to assist gymnasts in skill performance. However, empirical evidence on the role of gaze behavior and its interplay with movement behavior in complex skill performance in gymnastics is still limited and obvious gaps in the literature exist. Therefore, the aim of this study was the development of an eye-tracking prototype that allows for the measurement of gaze behavior during complex (aerial) skill performance. After presenting the structure and the analysis procedure of the system, two selected examples for the application of the system will be discussed.